Cytotoxic Assay of Nigella sativa Leaf Callus Extract (Thymol) on Hep-2 Cell Line Using ELISA Assay - Zaynab S. Abdel Gany; Mayasaa F. Mahdi (College of Pharmacy University of Baghdad, 2017)
Extract from cell culture of medicinal plant like Nigella sativa have been assessed for its cytotoxic properties. Thymol is likely responsible for the theraputic effects of  Nigella sativa leaf callus extract. In this short study the inhibitory effect of Nigella sativa leaf callus extract (Thymol) has been studied on Human Lorgnx Epidrmoid Carcinoma (Hep-2) cell line during different exposure period of time (24, 48 and 72 hrs.) using different concentration of the extract (1000, 500, 400, 300, 200 and 100 Âµg/ml). The optical density of the Hep-2 cells has been readed on 492 nm wave length. Thymol â€"induced cytotoxicity was (500 Âµg/ml) which inhibit cell growing compared to the control and this ratio increased at the 48 hrs of exopsure and stopped at 72 hrs. Key wards: Nigella sativa, callus extract, cell line, ELISA assay.